EVALUATION OF THE HOSPITAL STAFF'S RECEPTION OF PARENTS OF CHILDREN ADMITTED TO THE PEDIATRIC INTENSIVE CARE UNIT IN THE INTERIOR OF GOIÁS (CIPEEX, 2025)
The hospitalization of children in Pediatric Intensive Care Units (PICUs) poses significant challenges to parents, who face high levels of anxiety and stress. The care provided by hospital staff is essential to reduce the emotional impact and ensure family-centered care, promoting a more humane and positive experience for everyone involved. The objective of this study was to evaluate the reception of parents of children admitted to the Pediatric Intensive Care Unit by hospital staff. This was a cross-sectional, observational, analytical, qualitative, and quantitative study conducted between November 2023 and March 2024 with 30 parents of children admitted to the PICU of a hospital in the interior of Goiás. Sociodemographic questionnaires and the Portuguese version of the Critical Care Family Satisfaction Survey (CCFSS) were used to measure parents' satisfaction with the reception and quality of care provided by the hospital staff. Although all parents reported feeling welcomed by the hospital staff and 93.3% considered the care to be humane, 30% of parents expressed dissatisfaction with the noise level in the PICU, and 20% expressed uncertainty about the tranquility of the waiting room. These areas were identified as points that need improvement to enhance the experience of family members. It can therefore be observed that the reception at the PICU was well evaluated, but noise control and tranquility in the waiting room are aspects that require attention to ensure a more comfortable environment in line with the expectations of family members.
Keywords: Hospital reception; Pediatric Intensive Care Unit; Parent satisfaction; Humanization